2012
DOI: 10.1371/journal.pone.0032606
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Proteomic Profiling of Diapause in the Aphid Parasitoid Praon volucre

Abstract: BackgroundDiapause, a condition of developmental arrest and metabolic depression exhibited by a wide range of animals is accompanied by complex physiological and biochemical changes that generally enhance environmental stress tolerance and synchronize reproduction. Even though some aspects of diapause have been well characterized, very little is known about the full range of molecular and biochemical modifications underlying diapause in non-model organisms.Methodology/Principal FindingsIn this study we focused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
58
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 80 publications
(146 reference statements)
10
58
0
Order By: Relevance
“…Glycerol, the most commonly known polyol that is accumulated in cold-acclimated insects (Koštál et al, 2007;Lalouette et al, 2007), also decreased when acclimation temperature was cooled down to 4°C. These metabolic changes in the 4°C-exposed crustaceans were indicative of an alteration of the energetic metabolism, as already evidenced in some cold-acclimated insects (Colinet et al, 2012;Foray et al, 2013). The variations of intermediary compounds of the tricarboxylic acid cycle, which represent useful biomarkers of physiological adjustments in coldexposed arthropods (Michaud et al, 2008;Foray et al, 2013), together with the activity of the ATP-dependent sodium-potassium ion pump, should be examined in further studies to precisely document this cold-induced metabolic alteration.…”
Section: Temperature (°C)supporting
confidence: 70%
“…Glycerol, the most commonly known polyol that is accumulated in cold-acclimated insects (Koštál et al, 2007;Lalouette et al, 2007), also decreased when acclimation temperature was cooled down to 4°C. These metabolic changes in the 4°C-exposed crustaceans were indicative of an alteration of the energetic metabolism, as already evidenced in some cold-acclimated insects (Colinet et al, 2012;Foray et al, 2013). The variations of intermediary compounds of the tricarboxylic acid cycle, which represent useful biomarkers of physiological adjustments in coldexposed arthropods (Michaud et al, 2008;Foray et al, 2013), together with the activity of the ATP-dependent sodium-potassium ion pump, should be examined in further studies to precisely document this cold-induced metabolic alteration.…”
Section: Temperature (°C)supporting
confidence: 70%
“…[19][20][21][22][23][24][25] The present study descibes application of NMR-based metabolomics to characterise molecular and biochemical changes underlying diapause in the European corn borer Ostrinia nubilalis. We compared metabolomic profiles in polar hemolymph extracts of diapausing and non-diapausing larvae of O. nubilalis using high-resolution 1H-NMR spectroscopy, and show that diapause, as a special state of physiological dormancy, has a different metabolomic fingerprint compared to active non-diapausing phase.…”
Section: Resultsmentioning
confidence: 99%
“…Since comprehensive analysis of the metabolites present in an organism or cell is crucial to understanding cellular processes and function, reports describing metabolomic approaches for studying insect biochemistry have been gradually increasing over the past several years. [19][20][21][22][23][24][25] Metabolomics as a part of systems biology can reveal the unique fingerprint of low molecular weight metabolites within a biological sample that are characteristic for a specific physiological state. 26,27 In the present study, we analyzed metabolomic profiles in diapausing larvae of the European corn borer Ostrinia nubilalis (Lepidoptera: Crambidae), a maize pest species of Eurasia and North America.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these gross similarities, our quantitative bee-fly comparisons of coldrelated gene expression patterns (on both the transcript and GO levels) did not uncover significant overlaps. This may be attributable to speciesspecific molecular responses to cold, as suggested by a recent comparative study that also reported a lack of conserved gene expression related to dormancy between C. elegans , D. melanogaster , and S. crassipalpis (Ragland et al 2010;Colinet et al 2012). Alternatively, the lack of conservation may be explained by the fact that these studies examined different life stages and tissues (Table S5).…”
Section: Discussionmentioning
confidence: 95%
“…We characterize gene expression profiles of field-collected overwintering C. calcarata and contrast these against previously published active season gene expression profiles in the same species (Rehan et al 2014). Based on existing overwintering gene expression literature (Colinet et al 2007(Colinet et al , 2012Dunning et al 2013Dunning et al , 2014Lee et al 1998;Purac et al 2008;Ragland et al 2010;Rinehart et al 2007Rinehart et al , 2010Robich et al 2007;Torson et al 2015;Qin et al 2005;Yocum et al 2005Yocum et al , 2015, we predict that differential expression would be found in genes relating to heat shock proteins, membrane lipids, cuticular proteins, and cytoskeletal and muscular alterations. We also provide comparisons of our results to previous studies on overwintering gene expression and cold tolerance in other insects, in order to assess whether similar or different genes and pathways are associated with overwintering across taxa.…”
Section: Introductionmentioning
confidence: 96%